(untitled) (International Journal of Engineering and Computer Science, 2018)
With the globalization of IC outline ﬂow, numerous fables organizations outsource the creation of their plan to off-site foundries. As these foundries may not generally be believed, it brings about security vulnerabilities and dangers, for example, forging, IP theft, figuring out, overbuilding and Hardware Trojans. Logic encryption has developed to be a potential answer for secure the plan against these dangers. It presents some additional equipment (key-gates) into the plan to conceal the usefulness from unapproved clients, utilizing security keys. The areas of addition of key-gates decide the nature of the security gave by the subsequent plan. In this paper, we examined pros and cons of few papers and propose a productive technique to defeat the IP theft